Introduction. Confronting the challenges of the 21st Century - Cowling, Erin; Fernández, Esther; Nieto-Cuebas, Glenda Y. (My University, 2022)
We have compiled this collection from presenters at the 37th Annual Association for Hispanic and Classical Theater Symposium, which we had the privilege to organize in collaboration with the Festival de Teatro Clásico de Almagro in July 2021. The three lines of research on which we decided to center the conference are reflected in the articles of this issue of Comedia Performance: (1) Theater Practicalities: Innovation, translation, and pedagogical collaborations, (2) The Intersectional Comedia: Questions of Race, Gender, Class on the Stage, and (3) The Comedia under Siege: Confinements, Digitalization, and the Future.
Keywords: comedia; theater